The Myth of Cross-Cultural Love in Five Songs by Ebiet G. Ade: A Semiotic Study of Roland Barthes: Mitos Cinta Lintas Budaya dalam Lima Lagu Ebiet G. Ade: Semiotika Roland Barthes - Amirudin (Jurnal Casa Cendekia, 2026)
This study aims to interpret the cross-cultural myth of love in five songs by Ebiet G. Ade from the album "Puisi-Puisi Cinta Ebiet G. Ade" using Roland Barthes' semiotic framework. The analysis focuses on Camellia 1, Elegi Esok Pagi, Nyanyian Kasmaran, Cinta di Kereta Biru Malam, and Cintaku Kandas di Rerumputan. Employing a qualitative interpretive approach, the study examines denotative, connotative, and mythic levels of meaning. Rather than claiming direct cultural representation, the findings suggest that the songs can be read as resonating with multiple cultural value systems, including Javanese subtlety, action-oriented expressions associated with Buton cultural perspectives, and more explicit expressive tendencies often linked to Western contexts. The findings indicate that the songs can be read as articulating a cross-cultural myth of love that resonates with three cultural traditions: the subtlety and indirectness often associated with Javanese culture (Camellia 1), the appreciation of action and meaningful silence found in certain readings of Buton cultural values (Elegi Esok Pagi, Cintaku Kandas di Rerumputan), and the expressive boldness frequently linked to Western culture (Cinta di Kereta Biru Malam). The analysis also indicates that Nyanyian Kasmaran may be interpreted as a critique of excessively passive forms of emotional restraint through its emphasis on honesty and openness. The myth formulated is that love is nature's gift that flows like dew, but it will only become real if manifested with courage, even if that courage may lead to suffering, sin, or failure. This research contributes to the development of literary semiotics and cultural anthropology in Indonesia.